A disaggregate analysis of 'excess' car travel and its role in decarbonisation. (August 2022) - Wadud, Zia; Adeel, Muhammad; Anable, Jillian; Lucas, Karen
Highlights: The top 5% of car users travel nearly 27, 500 miles (4.8 times the average) and emit 5742 kg CO2 annually (5.7 times the average). The top 20% of car users in England travel 16, 740 miles and emit 3200 kg CO2 annually. Male, high-income professionals and large car owners are more likely to record higher mileage. Rationing the top 5% of car users would reduce emissions by 6.9% whilst rationing the top 20% would lead to reductions of 26%. Rationing high CO2 emitters directly is more effective than rationing car mileage. Abstract: This paper measures 'excess' car travel for its role in decarbonisation. On average, each English adult travels around 5, 680 miles a year and emits 1, 006 kg of CO2 . However, the top 5% 'excess' car users travel 4.8 times and emit 5.7 times the national average. Four binary logistic regression analyses were used to model the probability that people with specified characteristics belong to the 'excess' mileage and emitter groups. Results indicated that gender, employment and socio-economic status, household income (higher quintiles), company car availability, residential location and local population density were highly significant correlates of this 'excess' travel mileage. Multiple car ownership, business travel by car, multiple international flight frequencies and ownership of larger and diesel cars were positively associated with excess travel and emissions. A mileage rationing scheme targeting the top 20% users can cut emissions substantially (by 26%) compared to targeting 'excess' (top 5%) users only.